Lowered levels of colicin Ia membrane receptors in an Escherichia coli mutant defective in heme biosynthesis. - Gilchrist, M J (1976)
Cells of an Escherichia coli mutant defective in heme biosynthesis (hemA) grown under conditions for respiration deficiency (grown in the absence of aminolevulinic acid) have 20% of the number of specific colicin Ia receptors found in cells of the same strain grown under conditions for respiration competency (grown in the presence of aminolevulinic acid).